Effect of rhythmic auditory cueing on gait in people with Alzheimer disease - Wittwer, J.; Webster, K.; Hill, Keith (W.B. Saunders Co., 2013)
Objective: To determine whether rhythmic music and metronome cues alter spatiotemporal gait measures and gait variability in people with Alzheimer disease (AD). Design: A repeated-measures study requiring participants to walk under different cueing conditions. Setting: University movement laboratory. Participants: Of the people (NZ46) who met study criteria (a diagnosis of probable AD and ability to walk 100m) at routine medical review, 30 (16 men; mean age _ SD, 80_6y; revised Addenbrooke’s Cognitive Examination range, 26e79) volunteered to participate. Interventions: Participants walked 4 times over an electronic walkway synchronizing to (1) rhythmic music and (2) a metronome set at individual mean baseline comfortable speed cadence. Main Outcome Measures: Gait spatiotemporal measures and gait variability (coefficient of variation [CV]). Data from individual walks under each condition were combined. A 1-way repeated-measure analysis of variance was used to compare uncued baseline, cued, and retest measures. Results: Gait velocity decreased with both music and metronome cues compared with baseline (baseline, 110.5cm/s; music, 103.4cm/s; metronome, 105.4cm/s), primarily because of significant decreases in stride length (baseline, 120.9cm; music, 112.5cm; metronome, 114.8cm) with both cue types. This was coupled with increased stride length variability compared with baseline (baseline CV, 3.4%; music CV, 4.3%; metronome CV, 4.5%) with both cue types. These changes did not persist at (uncued) retest. Temporal variability was unchanged. Conclusions: Rhythmic auditory cueing at comfortable speed tempo produced deleterious effects on gait in a single session in this group with AD. The deterioration in spatial gait parameters may result from impaired executive function associated with AD. Further research should investigate whether these instantaneous cue effects are altered with more practice or with learning methods tailored to people with cognitive impairment.